PLANTAGO MAJOR FROM THE CANON OF AVICENE - Meliboeva Shohista Sharofiddin qizi (Scholars Digest Publishing, 2023)
Plantain greater L. leaves have been used for centuries as a wound healing agent in almost all parts of the world and in the treatment of a number of ailments besides wound healing. These include diseases related to the skin, respiratory organs, digestive organs, reproduction, circulation, against cancer, for pain relief and against infections. P. major contains biologically active compounds such as polysaccharides, lipids, caffeic acid derivatives, flavonoids, iridoid glycosides and terpenoids. Alkaloids and some organic acids have also been found. A number of biological activities have been found in plant extracts, including wound healing, anti-inflammatory, analgesic, antioxidant, mild antibiotic, immunomodulatory, and anti-ulcerogenic activity.
Keywords: Plantago major, Plantain large, use in folk medicine, phytochemical composition.